Getting the message. - Kariya, S.
Signals intelligence is a highly specialized and highly secret realm - and one where EEs are in high demand.
Keywords: US National Security Agency; Clandestine activities; Defense industry; Electrical engineers; Electromagnetic noncommunications transmissions; Electronic communications; Encryption; Foreign communication; Global eavesdropping; Intelligence gathering; Interception; Missile signals; Radar signals; Security clearance; Sensitive compartmented information; Signal detection; Signals intelligence; Technical challenges; Technical complexities